Evaluation of Stresses Generated with Two Different Self-Ligating Orthodontic Bracket Systems – A Finite Element Analysis - Mohit Awaradi; Roshan M. Sagarkar; Prashantha G Shivamurthy; Silju Mathew; Sharanya Sabrish; Nirajita Bhaduri (Indian Journal of Dental Research)
Aim To determine stresses generated in the posterior teeth region by two different self-ligating systems, 3M Unitek SmartClip and Damon Q Self-ligating brackets, using the finite element method (FEM). Methodology Computed tomography (CT) scan of maxilla was taken using Mimics software, and the Dicom data were imported into Hypermesh 13.0 software to convert it into a geometric model and then into FEM. Physical models of both the brackets were constructed and positioned on the teeth. Post archwire modeling, contact is defined between the bracket slot and 0.014” NiTi arch wire. The final assembled model was exported to ANSYS 12.1 for analysis, and 60 grams of load was applied at the ends of the arch wire. Results On using 0.014” CuNiTi in both the bracket systems, stresses generated on the root surface were found to be maximum on the first molar region, followed by the first premolar, second molar, canine, and second premolar regions. Comparison between the two bracket systems showed differences in the stresses generated, where higher stresses were generated at all regions in the Damon Q bracket system, except the inter-second premolar region. Conclusion Maximum stresses were observed with the 3M Unitek SmartClip bracket system at the second premolar cervical region when compared to the Damon Q system. In both the cortical bone and cancellous bone, maximum stresses were observed at the second premolar cervical in the Damon Q bracket system region.